STUDY LITERATURE REVIEW : TEORI SOSIAL FENOMENOLOGI DALAM RISET AKUNTANSI - Timothy Tanujaya,; Carmel Meiden, (JEMBA: JURNAL EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2024)
This research purpose to review the social theory literature, especially phenomenological theory. This research use the Systematic Literature Review (SLR) research method. To collect research data, the "Publish or Perish" application is used to collect journals related to the search settings on the Google Scholar site, distribution data from 2020 to 2021, the maximum number of search journals is 200, and the keyword used is "Social Theory" , “Phenomenology”, and “Accounting Practice”. From the search results, using certain criteria a total of 22 journals were collected related to phenomenological social theory research, however of the 22 only 7 journals mentioned the theoretical figures. The phenomena that occurred appeared most frequently in 2020 on PT and MSME sites or fields which raised the topic of pandemic and digitalization which had the most impact on the accounting context in interpreting business continuity and submitting financial reports in order to survive in the all-digital era or digitalization